E-011 Aneurysmal subarachnoid hemorrhage overnight: urgent or emergent intervention?. (23rd July 2022) - Akbik, F; Ermias, L; Williams, K; Takieddin, O; Grossberg, J; Tong, F; Cawley, C; Samuels, O; Sadan, O; Howard, B
Abstract : Introduction: Optimal timing of intervention after aneurysmal subarachnoid hemorrhage (aSAH) remains unclear. Practices vary from urgent/early intervention within a day of presentation to emergent/ultra-early occlusion upon presentation. While emergent intervention aims to minimize re-ruptures, this must be weighed against increased procedural risks and resource utilization. Here we compare the clinical course and outcomes of patients presenting during regular versus after-hours to determine whether timing of presentation drives disparities in outcomes. Methods: We performed a retrospective cohort study of aSAH patients admitted to a tertiary care center between January 1, 2012 through March 31, 2019. Patients were grouped based on the time of presentation during regular hours (0700hrs-1700hrs) vs. after-hours (1700hrs-0700hrs). Local practice for same-day intervention where feasible for regular hours presentation, patients presenting after-hours undergo treatment as the first case the following morning. Patients requiring emergent surgical decompression were excluded from analysis. Prospectively defined baseline characteristics, timing intervals, and clinical outcomes were compared. Results: 415 patients were included for analysis, 145 (34.9%) presenting during regular hours and 270 (65.1%) presenting during after-hours. Baseline demographics, latency to presentation, and severity of presentation where comparable between groups. Latency from presentation to initial angiography was shorter for regular versus after-hours presentations, with 30.3% vs. 14.% undergoing angiography within 4 hours of arrival (p<0.001). 71.2% vs. 74.0% underwent endovascular embolization. Aneurysmal re-rupture was rare in both cohorts (1.5% vs. 0.8%, not significant). Complications including cerebral vasospasm (52.4% vs. 52.8%, not significant) and radiographic delayed cerebral ischemia (DCI, 15.9% vs. 11.4%, p=0.070) were similar between cohorts, although there was a non-significant trend towards decreased DCI with after-hours presentation. In-hospital mortality and rates of good functional outcomes (defined as modified Rankin score of 0–2 at 1–6 months post discharge), were comparable between groups. After-hours presentation did not correlate with good functional outcome in multivariable binary logistic regression analyses accounting for age, latency from ictus, latency from admission to angiography, Hunt and Hess grade, Fisher grade, and smoking (aOR 0.83 [0.55 - 1.25], p=0.368). Conclusions: In this retrospective cohort study, timing of presentation did not correlate with in-hospital complications or long-term functional outcomes after aSAH. Although aneurysmal re-rupture is front-loaded in the ultra-early window, it is likely that this window has already passed by the time patients ultimately filter into a tertiary referral center. A practice of urgent and not-emergent aneurysmal occlusion did not lead to disparities in outcomes for patients presenting after-hours. Disclosures: F. Akbik: None. L. Ermias: None. K. Williams: None. O. Takieddin: None. J. Grossberg: None. F. Tong: None. C. Cawley: None. O. Samuels: None. O. Sadan: None. B. Howard: None.